ESTIMATING PRECISION OF SYSTEMATIC SAMPLING IN FOREST INVENTORIES - Mello,José Marcio de (2015)
The sampling technique commonly used in forest inventories is the systematic sampling. This study aimed to evaluate the estimator of the variance of the mean proposed by Cochran for a systematic sampling technique in forests with high and low percentages of the sampled area. The study areas comprised native vegetation in Minas Gerais. To assess the efficiency of the estimators in situations involving high sampling rates (determined as the percentage of the area sampled), a fragment where a census was conducted was used. The remaining fragments comprised situations involving low sampling rates, and for these fragments, inventory accuracy was determined using the Cochran estimator. As a result it was observed, in the fragment where the census was conducted, that the structure of the correlation coefficient proposed by Cochran remained approximately constant for the area, and to the extent that sampling rate reduced, the impact of the Cochran estimator on the inventory accuracy decreased. For the fragments with a low sampling rate, it could be inferred that the sampling rate was a key factor for the correlation proposed by Cochran to have an impact on the forest inventory accuracy. The use of this estimator is indicated for fragments with a sampling rate greater than 10% of the area.